Informed consent: analysis of the level of knowledge of medical professionals from Maranhão - Murad Neto, Abdon José; Ferreira, Evaldo César Macau Furtado; Cutrim, Patrícia Travassos; Ribeiro, Carlos Henrique Bento; Oliveira, Andrieli Barros; Pestana, Ricardo Henrique Oliveira; Pires, Cibelle Dutra; Brito, Luciane Maria Oliveira (Medicina (Ribeirao Preto), 2015)
Design of the Study: Analytical cross-sectional observational study. Introduction: The Informed Consent (IC) is expressed by respect for human dignity requires that all research occurs after informed consent of the subjects, individuals or groups, by themselves and/or their legal representatives express their agreement to participate in the research. However, despite its extreme importance, it is observed that its use is not common in ordinary practice of medicine in our country, because the knowledge about this instrument is still incomplete of many doctors, that consists of a fundamental right of the patient and a ethical requirement for medicine. Objective: Investigate the level of knowledge about the Informed Consent by medical professionals active in Maranhão. Methodology: This is a cross-sectional analytical study with physicians in activity in the period from December 2012 to October 2013. A questionnaire consists of 18 questions about The Informed Consent was sent to 368 doctors who had registered email at the Regional Council of Medicine. Results: 170 (46,2%) questionnaires were answered. The level of knowledge about the IC was rated as average to 83,5% of physicians. Most of participants were specialists (85,7%) and 96,4% correctly recognized that the IC is a right of the patient. When asked about the main function of Informed Consent, 65,9% chose the wrong statement. It was noticed that all interviewees did not know how to proceed when delivering the IC to the patient. Conclusions: The doctors evaluated had a deficient knowledge of the IC, even being rated as average, had flaws in its use and in some main aspects of this term, as its main function and the ability to consent